Generation and characterization of a population of Tagetes minuta of broad genetic base: Obtaining selected individuals - Massuh, Yamile (2017)
Tagetes minuta L. (Asteraceae) is an annual herb that is of great interest due to the bioactive properties of its essential oil (EO)and its industrial use. In Argentina, 0.5 tons/year of EO are obtained from wild populations and commercialized with a value of 80-120US$/kg. The introduction of the species in culture, and the initiation of a process of domestication, selection and breeding material aimedat generating higher yields and quality of EO as an alternative to wildcollection. The goal of this work was to generate a population with abroad genetic base to obtain high phenotypic variability, and characterize the individuals morphologically and chemically, thus identifying and selecting those with outstanding characteristics. From seeds obtained by free crossing of plants of different provenances grown in a preliminary test, a population of broad genetic base was generated in an experimental plot. Quantitative and qualitative morphological traits were measured in all plants and the selection criteria were defined to form a selected population. The morphological selection criteria(height, plant structure and Nº of branches) were met by 26% of the evaluated plants, of which 2.7% presented interesting EO compositions(selected individuals). Descriptive, principal components and correspondence analysis were made. Great variability in the population of broad genetic base was found regarding the analyzed characters.Since our character definitions allowed to compare and differentiate the evaluated plants, they were considered as good descriptors of the species. The selected individuals were differentiated morphologically into two groups and chemically into three groups, which differed in their EO main compounds. The selection of these individuals constitutes the initial stage of this ongoing work that will enable us to continue the process of domestication and breeding of the species oriented to obtain selected chemotypes.